Coping with COVID: pandemic narratives for Australian children. Issue 5 (May 2022) - Gildersleeve, Jessica; Cantrell, Kate; Bryce, India; Daken, Kirstie; Durham, Jo; Mullens, Amy; Batorowicz, Beata; Johnson, Rhiannan
Abstract: The experience of the COVID-19 pandemic can be recognised as traumatic for the way in which its sudden and unexpected onset disrupted a sense of ordinary life for so many around the world. Adults, and far less so children, were unable to prepare for the danger of the rapidly spreading disease. As such, both were left vulnerable to the experience of trauma and anxiety that surrounds the threat of COVID. Whereas adults, however, have access to a range of resources and strategies for mental health protection, children of various ages need targeted resources to enable them to understand, prepare for, and come to terms with a trauma situation. A great deal of research exists around the value of children developing their own narratives as a means of coming to terms with trauma, such that storytelling is identified as a primary coping device. Similarly, literature exists that compares parental narratives of trauma with those of their children. Moreover, the use of the fairy tale as a cautionary tale has long been examined. What has not been established is the way in which contemporary multimedia narratives – such as television programmes, animations, and digital stories – can be used to develop coping strategies in children and to mitigate anxiety in young people experiencing global or collective trauma. This article examines a selection of such narratives produced for Australian children during the COVID-19 pandemic. Through a cross-disciplinary framework, this work considers how these resources can help (or hinder) mental health recovery in young children under the age of five, as well as strategies for best practice in the future development of trauma-informed resources for this age group. Abstract : COVID-19; Storytelling; Pandemic narratives; Digital stories; Children's health; Children's wellbeing; Emergency and disaster recovery.